ANALISIS NILAI – NILAI KARAKTER DALIHAN NA TOLU PADA MASYARAKAT BATAK TOBA DI KOTA JAMBI - Rohani Maranatha Aritonang; Firman; Heri Usmanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of modernization and globalization has caused changes in mindsets and shifts in cultural values in people's lives, including among the Toba Batak people who live in diaspora. This phenomenon can affect the sustainability of the process of inheriting cultural values contained in the Dalihan Na Tolu philosophy to the younger generation. This study aims to examine the character values contained in Dalihan Na Tolu and describe the forms of application and various challenges faced by the Toba Batak people in Jambi City in maintaining these values. This study uses a qualitative method with a descriptive case study approach. Research informants were determined through a purposive sampling technique involving traditional figures, traditional leaders, parents, and the younger generation of the Toba Batak community. Data collection was carried out through observation, interviews, and documentation, then analyzed using the Miles and Huberman interactive analysis model. The results of the study indicate that the Dalihan Na Tolu philosophy contains five main character values, namely religious, nationalist, independent, mutual cooperation, and integrity. These values are still manifested in various traditional activities, family life, and social relationships in the community. However, preservation efforts face a number of challenges, such as the declining interest of the younger generation in traditional culture and the increasing influence of digital technology and foreign cultures.